Articulating theory and practice and producing innovation in the professional master's degree program in Health Sciences Teaching - Liberman, Flavia; Frutuoso, Maria Fernanda Petroli; Lima, Laura Camara; Mendes, Rosilda; Acosta, Ana Rojas (Saúde e Sociedade, 2015)
This paper aims to analyze the experience of the discipline "Grupo de Estudos e Pesquisas sobre as Práticas" (GEPPRA - Study and Research Group on Practices) of the Professional Master's Degree Program in Health Sciences Teaching of the Federal University of São Paulo (UNIFESP), Baixada Santista Campus. The focus was on the scribe method and its strong points as a teaching-learning method and as a source of reflection. The analyzed corpus was composed of fourteen texts written by students and professors. The analysis stages were: automatic pragmatic analysis of the texts with the aid of the Alceste software; content analysis of passages that contained the following keywords: Geppra (Geppra I, Geppra II), Scribe (written, write) and Work (action, practice and reflection), in order to identify some of the meanings attributed to GEPPRA; the scribe method; and effects of this discipline in the professional practice. Results show that it was possible to build a new network textuality collectively, based on a reflective experience, with exchanges, discussions and questionings concerning ways to deal with challenging work scenarios. This study shows that the scribe methodology is a powerful tool that can be used in other professional education contexts or group processes, both academic and/or clinical.